Penambahan Sari Akar Eceng Gondok (Eichornia crassipes) Media MS pada Pertumbuhan Tahap Subkultur I Anggrek Bulan (Phalaenopsis sp.) - Ngadiani Ngadiani; Vivin Andriani; Aulia Rahmawati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Moon Orchid (Phalaenopsis sp.) is an ornamental plant that has attractive flowers and has economic value. Cultivation can be optimized by modifying the MS medium. The addition of natural growth regulators with the right concentration can support the success of tissue culture and can also reduce costs. This study aims to determine the addition of water hyacinth root extract in the first subculture stage of the moon orchid. This study used a factorial completely randomized design with 4 treatments and 6 replications, namely: MS0 (MS medium), MS1 (MS medium + 10% water hyacinth root extract), MS2 (MS media + 15% water hyacinth root extract), and MS3 (MS medium + 20% water hyacinth root extract). Observation variables included: number of leaves, number of roots, and plantlet height. The results showed that there was an interaction between MS media and the addition of water hyacinth root extract in the first subculture stage of the moon orchid on MS3 media (MS media + 20% water hyacinth root extract) indicating optimal results on the three parameters, namely: number of leaves 5, 2 strands, the number of roots 5.8 fruit, and plantlet height 2.3 cm.